Comprehensive dietary patterns explain acquired cystic kidney disease risk through genetic and metabolomic mechanisms - Xu, Chenhao; Zhao, Junjie; Wu, Kan; Liu, Shengzhuo; Zhang, Fan; Cao, Qin; Wan, Zhouwei; Tang, Yongquan; Liu, Zhihong; Zeng, Hao; Wang, Xianding; Liang, Jiayu (Frontiers in Nutrition, 2025)
BackgroundAcquired renal cysts (ARC) are associated with kidney function decline, necessitating novel dietary pattern (DP) analyses in large cohorts.MethodsThis UK Biobank prospective cohort study (2006–2010) included participants with ≥2 dietary records, excluding those with severe kidney damage. The constructed comprehensive dietary pattern integration (CDPI) utilized reduced rank regression (RRR) and latent profile analysis (LPA). ARC cases (ICD-10: N28.1) were assessed via Cox regression for risk and dose–response, with NMR metabolites examined as mediators.ResultsAmong 119,709 participants (median follow-up: 10.57 years), 850 ARC cases were identified. Lipid-rich and hyperglycemic diets increased ARC risk [e.g., HRs for G1.DP1: 1.080 (1.024, 1.139); G1.DP2: 1.144 (1.048, 1.249)], while micronutrient-rich diets showed weak protective effects [G4.DP1: 0.943 (0.892, 0.998)]. LPA confirmed RRR findings, and 7/251 NMR metabolites had significant mediating effects.ConclusionDiets high in fat (cheese, butter, pizza) and sugar (chocolate, sugary drinks) elevated ARC risk, whereas micronutrient- and fiber-rich diets (vegetables, fruit, lean poultry, nuts, eggs) were protective. Key mediators included branched-chain amino acids, IGF-1, and RBC distribution width.